The 7 Day Railway - Forrest, Alex (2008)
Network Rail, the not-for-dividend company formed by the government in 2002, owns and maintains the national railway infrastructure; essentially the tracks, signalling equipment and stations & structures. The company's main revenue stream is derived from selling, in other words the routes and times for running trains by the passenger and freight train operators. The greatest obstacle to achieving growth and increasing revenue is the frequent blockages (known as 'possessions' within the rail industry) to routes that are necessary to allow maintenance and renewal of the infrastructure. The most disruptive of these blockages takes place when a renewal of a switch & crossing (the part of the track that enables a train to change from one line to another, known as and referred to in this document as the 'S&C') is needed.